2008
DOI: 10.1111/j.1349-7006.2007.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mitochondria‐involved apoptosis in estrogen receptor‐negative cells by a novel tamoxifen derivative, ridaifen‐B

Abstract: Tamoxifen is an antagonist of estrogen receptor, which is used widely as an estrogen receptor-positive breast cancer drug that blocks growth signals and provokes apoptosis. However, recent studies have revealed that tamoxifen induces apoptosis even in estrogen receptor-negative cells. In the present study, we synthesized several tamoxifen derivatives to augment the apoptosis-inducing effect of tamoxifen and evaluated the apoptosis-inducing pathway. The estrogen receptor-positive human leukemia cell line HL-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Moreira et al [280] demonstrated that TAM interacted with the flavin mononucleotide site of complex I, leading to mitochondrial failure. Ridaifen-B, a novel TAM derivative, has been shown to induce apoptosis in ER-negative breast cancer cells by reducing mitochondrial membrane potential [281]. Pancratistatin (PST), a natural compound obtained from the Hawaiian spider lily, has been known to be specific and selective in inducing apoptosis in multiple cancer cell lines.…”
Section: Physiological and Pathological Implicationsmentioning
confidence: 99%
“…Moreira et al [280] demonstrated that TAM interacted with the flavin mononucleotide site of complex I, leading to mitochondrial failure. Ridaifen-B, a novel TAM derivative, has been shown to induce apoptosis in ER-negative breast cancer cells by reducing mitochondrial membrane potential [281]. Pancratistatin (PST), a natural compound obtained from the Hawaiian spider lily, has been known to be specific and selective in inducing apoptosis in multiple cancer cell lines.…”
Section: Physiological and Pathological Implicationsmentioning
confidence: 99%
“…Binding of OH-TAM to ERa leads to a decrease in tumor cell growth [6]. OH-TAM is also effective in the absence of ER expression in breast cancer, melanoma, glioma and pancreatic carcinoma [7][8][9]. However this non-genomic effect (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed mechanism for RID-B-mediated cancer cell growth inhibition and apoptosis is unknown, the following mechanism was indicated from the present findings: RID-B may activate caspase-3 to induce DNA fragmentation, and RID-B may directly bind to DNA to inhibit DNA synthesis. It has been reported that RID-B reduced mitochondrial membrane potential during the induction of apoptosis in the human lymphoid helper T-cell line Jurkat (11), and that RID-B induced microtubule-associated protein 1A/1B-light chain 3 and lysosome colocalization resulting in autophagy in Jurkat cells (12). Additionally, the current data revealed that caspase inhibitor, Z-VAD-FMK, partially suppressed RID-B-mediated growth inhibition and DNA fragmentation in Huh-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…1), and has been observed to elicit marked cellular damage against both ER-positive and -negative tumor cells (11). It has also been reported that RID-B induces autophagy in the ER-negative human leukemia Jurkat cell line (12).…”
Section: Introductionmentioning
confidence: 98%